Exploring Seasonal Patterns in Diet-Related Characteristics and Their Consequences on Obstructed Urolithiasis in Household Livestock - R Murugan, Dhwani Bartwal, Aishwary Awasthi (Revista Electronica de Veterinaria, 2024)
The term obstructed urolithiasis refers to the formation of urinary stones leading to blockages and the study aims to discern how seasonal dietary patterns can contribute to the occurrence and severity of this condition in household livestock. The present research effort attempted to investigate the occurrence of Obstructed Urolithiasis in Household Livestock such as cattle, goats, horses, sheep and pigs. In the academic year term from May 2019 to April 2020, 810 occurrences were recorded in our study. In comparison with other domesticated livestock, cattle had the greatest occurrence (27.16%). Cattle have been found to be the most affected of the various kinds of animals, followed by goats. There is a strong link among the incidence of obstructive urolithiasis and seasonally, with the highest number of occurrences recorded in the wintertime seasons of December to February. In urolithiasis-affected livestock, the female to-male proportion was, cattle have an occurrence rate of (27.16%), goats have an occurrence rate of (21.85%) and other species in a decreasing sequence include sheep (18.64%), horse (16.17%) as well as pig (16.17%), suggesting a greater incidence in animals of males. Most of the cattle (27.16%) and goats (21.8%) with obstructed urination were similarly administered a grain-rich, high-phosphorus diets, which contributed to Urinary calculus development. The significance of changes in behavior related to seasonal shifts and the livestock’s food condition in the development of urolithiasis is substantial. This interaction among the season and dietary imbalances is going to raise the frequency of obstructive urolithiasis in household livestock.